Chemical constituents and bactericidal and fungicide potential of the essential oil of Pimenta dioica Lindl against pathogenic microorganisms - Everton, Gustavo O. (2021)
Fil: Everton, Gustavo O. Universidade Federal do Maranhão. Laboratório de Pesquisa e Aplicação de Óleos Essenciais; Brasil.